INTEGRATION OF DIGITAL INTELLIGENCE IN EDUCATION CURRICULUM - Erna Widyasari; Achmad Fathoni; Sutama Sutama; Al-Amin; Mohammad Ahmad Bani Amer (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to examine the integration of digital intelligence in the education curriculum by investigating how elements of digital intelligence can be incorporated to support the development of 21st century skills. Through the literature research method, this study collected and analyzed data from various related articles according to the research context. The results showed that the effective integration of digital intelligence into the curriculum requires structural changes and a holistic approach that includes curriculum development, teacher training, and infrastructure changes. The study noted the importance of encouraging students to become not only competent users of technology but also ethical and responsible digital citizens. In addition, it was found that administrative support, collaboration among teachers, and partnerships with parents and communities play an important role in strengthening the implementation of digital intelligence in the curriculum. The conclusion of the study underscores the need for dynamic adaptation of the curriculum to maintain relevance with the ever-changing technological developments.